A Review of Aseptic Loosening in Total Hip Arthroplasty - El-Warrak, A. O.; Olmstead, M. L.; von Rechenberg, A.; Auer, J. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Total hip arthroplasty has gained worldwide acceptance over the last few decades in humans and in dogs. Although long-term success is high in most studies, aseptic loosening of components is still a serious complication. Aseptic loosening can affect either the acetabular or femoral component of both cemented and cementless systems. The process is usually characterized by an interface membrane which develops between the adjacent bone and bone cement of the prosthesis, or in cementless components, between the bone and the implant itself. The process leading to the formation of this interface membrane and its function is still unclear; although much has been written about this topic in recent years. Biomechanical factors including: prosthesis design and material composition and cellular mechanisms such as signaling pathways of cytokines, local mediators or matrix metalloproteinases, have been incriminated to be responsible for the process. None of these factors, alone, have been conclusively proven to be the cause of aseptic loosening.Aseptic loosening is the major cause of implant failure in total hip arthroplasty. The controversial aspects of the pathogenesis of the process are reviewed. The role of biomechanical factors, including prosthesis design, material composition and biological factors, such as inflammatory mediators, cellular mechanisms, cytokines and matrix metalloproteinases, are detailed.
Keywords: Aseptic loosening; hip arthroplasty; implant failure